Yttria-stabilized zirconia ceramic material and preparation method thereof, and electronic equipment
By introducing a matrix layer and a reinforcing layer into yttrium-stabilized zirconia ceramic material, and forming a compressive stress layer through sandblasting, the problem of easy cracking of yttrium-stabilized zirconia ceramic back covers during drops was solved, and the mechanical strength of the ceramic was improved.
Patent Information
- Application Number
- CN202210600910.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-05-30
AI Technical Summary
Existing yttrium oxide stabilized zirconia ceramic back covers are prone to cracking when subjected to drops, making it difficult to meet the high-strength usage requirements of mobile smart devices.
Yttrium-stabilized zirconia ceramic material with a matrix layer and a reinforcing layer is used. The monoclinic phase content in the matrix layer is 0.1-8%, and the monoclinic phase content in the reinforcing layer is 5-40%. A compressive stress layer is formed on the ceramic surface by sandblasting to prevent crack initiation or propagation.
The mechanical strength of ceramics has been improved, requiring a greater impact force to break in the event of a mechanical collision, thus meeting the requirements for use in mobile smart devices.
Smart Images

Figure CN117185807B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of yttria-stabilized zirconia ceramic materials. Background Art
[0002] At present, with the advent of the 5G era, new requirements have been put forward for the back cover materials of mobile smart devices, especially in terms of the signal transmission performance of the materials. Traditional metal materials will produce electromagnetic shielding effects and cannot meet the requirements. Yttria-stabilized zirconia ceramic materials are increasingly used due to their excellent mechanical properties, warm feel, and excellent signal penetration performance.
[0003] Yttria-stabilized zirconia ceramic material, as the back cover material of mobile smart devices, has high requirements for performance. However, the existing yttria-stabilized zirconia ceramic back cover is prone to cracks when dropped. Therefore, it is necessary to develop a ceramic material with higher strength to meet the usage requirements of mobile smart devices. Summary of the invention
[0004] In view of this, the present application provides a yttria-stabilized zirconia ceramic material and a preparation method thereof. The yttria-stabilized zirconia ceramic material has higher strength than the yttria-stabilized zirconia ceramic material in the prior art and can meet the strength requirements of the back cover of mobile smart devices for the material.
[0005] The present invention provides an yttria-stabilized zirconia ceramic material, which comprises a matrix layer and at least one strengthening layer adjacent to the matrix layer, wherein the crystal phase of the ceramic material comprises a monoclinic phase and a tetragonal phase, wherein the weight percentage of the monoclinic ceramic in the matrix layer is 0.1-8% of the ceramic material of the matrix layer, the weight percentage of the monoclinic ceramic in the strengthening layer is 5-40% of the ceramic material of the strengthening layer, the monoclinic phase content in the matrix layer is 2%-20% of the monoclinic phase content in the strengthening layer, and the thickness of the strengthening layer is 0.5-5 μm.
[0006] Optionally, the yttria content in the yttria-stabilized zirconia ceramic material is 2.1 mol%-3.2 mol%, the colorant molar ratio is 0-5%, and the rest is zirconia.
[0007] Preferably, the monoclinic phase content of the matrix layer is 0.1-3%, the monoclinic phase content on the surface of the strengthening layer is 5-30%, and the monoclinic phase content in the matrix layer is 2%-18% of the monoclinic phase content in the strengthening layer.
[0008] Preferably, the strengthening layer has a thickness of 0.5-3 μm.
[0009] Preferably, the yttria content in the yttria-stabilized zirconia ceramic material raw material is 2.5 mol%-3 mol%, and the zirconia content is 97 mol%-97.5 mol%.
[0010] The present invention provides a method for preparing the above-mentioned yttria-stabilized zirconia ceramic material, comprising the following steps:
[0011] (1) forming a yttrium-stabilized zirconia ceramic raw material into a ceramic matrix blank, and sequentially performing degreasing and sintering treatments on the ceramic matrix blank to obtain a ceramic sheet;
[0012] (2) The ceramic sheet is subjected to rough sandblasting treatment. When sandblasting, a spherical sandblasting material with an average particle size of 10-300 μm is selected. The sandblasting direction is at an angle of 30-90° to the surface of the ceramic sheet to be treated. The sandblasting time is 5-180 s and the working pressure during sandblasting is 0.1-1.0 MPa.
[0013] (3) The surface of the ceramic sheet obtained by the sandblasting is finely polished, and the roughly polished ceramic sheet is finely polished on a polishing machine with a polishing paste or a polishing solution in the polishing machine until there are no scratches on the sample surface, thereby obtaining the yttria-stabilized zirconia ceramic material of the present invention.
[0014] Optionally, in step (1), the sintering temperature is 800°C-1400°C, and the sintering time is 0.5-4h.
[0015] Optionally, in step (2), the sandblasting material is one or more of alumina, silicon carbide, zirconium oxide, and zirconium oxide toughened alumina.
[0016] Optionally, in step (3), the grinding paste or polishing grinding solution contains one or more of aluminum oxide, silicon oxide, and diamond.
[0017] The present invention also provides an electronic device, wherein at least some components of the electronic device are made of the above-mentioned yttria-stabilized zirconia ceramic material.
[0018] The inventors of the present invention have discovered through a large number of experiments that a yttria-stabilized zirconia ceramic material comprises a matrix layer and at least one strengthening layer adjacent to the matrix layer, wherein the crystal phase of the ceramic material is a mixture of a monoclinic phase and a tetragonal phase, wherein the weight percentage of the monoclinic phase ceramic in the matrix layer is 0.1-8% of the ceramic material of the matrix layer, the weight percentage of the monoclinic phase ceramic in the strengthening layer is 5-40% of the ceramic material of the strengthening layer, the monoclinic phase content in the matrix layer is 2%-20% of the monoclinic phase content in the strengthening layer, that is, the monoclinic phase content in the strengthening layer is higher than the monoclinic phase content in the matrix layer, the strengthening layer is obtained by phase change of a ceramic having the same crystal phase as the ceramic in the matrix layer, when the tetragonal phase in the strengthening layer changes into the monoclinic phase, it will cause volume expansion, and by controlling the monoclinic phase content in the strengthening layer, a compressive stress layer with a certain thickness is formed on the surface of the ceramic, and the presence of the compressive stress layer will prevent the generation or propagation of cracks when the ceramic is impacted by an external force. This means that compared with yttria-stabilized zirconia ceramics having a monoclinic phase content of 0.1-8%, the zirconia ceramics of the present invention with a strengthening layer require a greater collision force to be damaged when a mechanical collision occurs, thereby effectively improving the strength of the ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the structure of the yttria-stabilized zirconia ceramic material prepared in Example 1 of the present application.
[0020] The reference numerals are as follows: 1 - reinforcement layer; 2 - matrix layer. DETAILED DESCRIPTION
[0021] The technical solution of the present application is described in detail below with reference to the accompanying drawings.
[0022] The present application provides a yttria-stabilized zirconia ceramic material, the ceramic material comprising a matrix layer 2 and at least one strengthening layer 1 adjacent to the matrix layer 2. Preferably, Figure 1 As shown, there are two strengthening layers 1 adjacent to the ceramic material and the matrix layer. The crystal phase of the ceramic material contains a monoclinic phase and a tetragonal phase, wherein the monoclinic phase content of the matrix layer is 0.1-8% by weight, the monoclinic phase weight percentage of the surface of the strengthening layer is 5-40%, the monoclinic phase content in the matrix layer is 2%-20% of the monoclinic phase content in the strengthening layer, and the thickness of the strengthening layer is 0.5-5 μm.
[0023] The inventors of the present invention have discovered through a large number of experiments that a yttria-stabilized zirconia ceramic material comprises a matrix layer and at least one strengthening layer adjacent to the matrix layer, wherein the crystal phase of the ceramic material contains a monoclinic phase and a tetragonal phase, wherein the weight percentage of the monoclinic phase ceramic in the matrix layer is 0.1-8% of the ceramic material of the matrix layer, the weight percentage of the monoclinic phase ceramic in the strengthening layer is 5-40% of the ceramic material of the strengthening layer, the monoclinic phase content in the matrix layer is 2%-20% of the monoclinic phase content in the strengthening layer, that is, the monoclinic phase content in the strengthening layer is higher than the monoclinic phase content in the matrix layer, volume expansion will be caused when the tetragonal phase in the strengthening layer is transformed into the monoclinic phase, and a compressive stress layer with a certain thickness is formed on the surface of the ceramic by controlling the monoclinic phase content in the strengthening layer, and the presence of the compressive stress layer will prevent the generation or propagation of cracks when the ceramic is impacted by an external force. This means that compared with yttria-stabilized zirconia ceramics having a monoclinic phase content of 0.1-8%, the zirconia ceramics of the present invention with a strengthening layer require a greater collision force to be damaged when a mechanical collision occurs, thereby effectively improving the strength of the ceramics.
[0024] A method for preparing a phase change content change of a ceramic surface with a monoclinic phase content higher than that of a matrix layer, the present invention adopts sandblasting to control the monoclinic phase content and phase change depth of the ceramic surface. Yttria-stabilized zirconia ceramic material will transform from a tetragonal phase to a monoclinic phase under the action of external mechanical stress, accompanied by a certain volume expansion. Zirconia after surface sandblasting forms a compressive stress layer with a certain thickness on the ceramic surface due to phase change volume expansion. The presence of the stress layer will prevent the generation or propagation of cracks when the ceramic is impacted by an external force. This means that compared with untreated ceramics, zirconia ceramics require a greater collision force to break when a mechanical collision occurs, which effectively improves the strength of the ceramic. It can be understood that the monoclinic phase content of the matrix layer is 0.1-8% by weight, the monoclinic phase weight percentage of the surface of the strengthening layer is 5-40%, the monoclinic phase content in the matrix layer is 2%-20% of the monoclinic phase content in the strengthening layer, and the thickness of the strengthening layer is 0.5-5 μm, which meets the requirements of the present invention for ceramic strength. The inventors of the present invention found that although by controlling the preparation method, a yttria-stabilized zirconia ceramic material with a higher monoclinic phase content in the strengthening layer and a thicker strengthening layer can be obtained, the inventors of the present invention found that at this time, the surface of the strengthening layer has large scratches on the surface of the ceramic due to sandblasting for too long or too high an intensity, which affects the appearance and mechanical strength of the product and does not meet the requirements of industrialized products.
[0025] The present invention controls the monoclinic phase content and phase change depth of the ceramic surface by sandblasting the surface of the yttria-stabilized zirconia ceramic material and controlling the sandblasting conditions. Under the action of external mechanical stress, the yttria-stabilized zirconia ceramic material will transform from the tetragonal phase to the monoclinic phase with a certain volume expansion. The zirconia after surface sandblasting forms a compressive stress layer with a certain thickness on the ceramic surface due to the volume expansion of the phase change. The presence of the stress layer will prevent the generation or propagation of cracks when the ceramic is impacted by external forces. This means that compared with untreated ceramics, when a mechanical collision occurs, the zirconia ceramic requires a greater collision force to be damaged, which effectively improves the strength of the ceramic. It can be understood that the monoclinic phase content of the matrix layer is 0.1-8% by weight, the monoclinic phase weight percentage of the surface of the strengthening layer is 5-40%, the monoclinic phase content in the matrix layer is 2%-20% of the monoclinic phase content in the strengthening layer, and the thickness of the strengthening layer is 0.5-5 μm, which meets the requirements of the present invention for ceramic strength. The inventors of the present invention found that although a yttria-stabilized zirconia ceramic material with a higher monoclinic phase content and a thicker strengthening layer can be obtained by controlling the preparation method, the inventors of the present invention found that at this time, the surface of the strengthening layer is sandblasted for too long or the sandblasting intensity is too high. Although the thickness of the surface strengthening layer will increase accordingly, larger scratches will appear on the ceramic surface, which will affect the appearance and mechanical strength of the product and fail to meet the needs of industrialized products.
[0026] If the sandblasting time is too short or the sandblasting intensity is too low, it will lead to the disadvantages of thick bottom of the strengthening layer and low content of monoclinic ceramic in the strengthening layer.
[0027] Optionally, the yttria content in the yttria-stabilized zirconia ceramic material is 2.1 mol%-3.2mol%, the colorant molar ratio is 0-5%, and the rest is zirconia. The yttria-stabilized zirconia ceramic material used in the present invention is a common yttria-stabilized zirconia ceramic material for those skilled in the art, and will not be described in detail here. The colorant used is also a common ceramic colorant in the art, and will not be described in detail here.
[0028] Preferably, the monoclinic phase content of the matrix layer is 0.1-3%, the monoclinic phase content on the surface of the strengthening layer is 5-30%, and the monoclinic phase content in the matrix layer is 2%-18% of the monoclinic phase content in the strengthening layer.
[0029] Preferably, the strengthening layer has a thickness of 0.5-3 μm.
[0030] Preferably, the yttria content in the yttria-stabilized zirconia ceramic material raw material is 3 mol%, and the zirconia content is 97 mol%.
[0031] The present invention provides a method for preparing the above-mentioned yttria-stabilized zirconia ceramic material, comprising the following steps:
[0032] (1) forming a yttrium-stabilized zirconia ceramic raw material into a ceramic matrix blank, and sequentially performing degreasing and sintering treatments on the ceramic matrix blank to obtain a ceramic sheet;
[0033] (2) The ceramic sheet is subjected to rough sandblasting treatment. When sandblasting, a spherical sandblasting material with an average particle size of 10-300 μm is selected. The sandblasting direction is at an angle of 30-90° to the surface of the ceramic sheet to be treated. The sandblasting time is 5-180 s and the working pressure during sandblasting is 0.1-1.0 MPa.
[0034] (3) The surface of the ceramic sheet obtained by the sandblasting is finely polished, and the roughly polished ceramic sheet is finely polished on a polishing machine with a polishing paste or a polishing solution in the polishing machine until there are no scratches on the sample surface, thereby obtaining the yttria-stabilized zirconia ceramic material of the present invention.
[0035] The inventors of the present invention have found through a large number of experiments that by using spherical blasting materials with an average particle size of 10 to 300 μm for sandblasting and controlling the sandblasting angle, duration, and working pressure conditions, a ceramic material with higher strength can be formed in the yttria-stabilized zirconia ceramic material.
[0036] Optionally, in step (1), the sintering temperature is 800°C-1400°C, and the sintering time is 0.5-4h. The sintering temperature and sintering time are common sintering temperatures and times for sintering ceramics, and are not described in detail here.
[0037] Optionally, in step (2), the sandblasting material is one or more of aluminum oxide, silicon carbide, zirconium oxide, and zirconium oxide toughened aluminum oxide. The above-mentioned sandblasting materials are the sandblasting materials selected by the inventors of the present invention after a large number of experiments.
[0038] Optionally, in step (3), the abrasive paste or polishing grinding solution contains one or more of aluminum oxide, silicon oxide, and diamond. The abrasive paste or polishing grinding solution is a common abrasive paste or polishing grinding solution for those skilled in the art, and will not be described in detail here.
[0039] The present invention also provides an electronic device, wherein at least some components of the electronic device are made of the above-mentioned yttria-stabilized zirconia ceramic material.
[0040] The electronic device includes a terminal device, specifically, a smart phone, a smart watch and other electronic devices.
[0041] The technical solution of the present application is described in detail below in multiple embodiments.
[0042] Example 1
[0043] (1) Forming of ceramic matrix blank: Yttria-stabilized zirconia injection molding feed is put into an injection molding machine, and a ceramic matrix blank is prepared by injection molding. The injection molding conditions are: injection molding temperature is 210°C, injection molding pressure is 100 MPa, and holding pressure is 100 MPa. Degreasing treatment: The degreasing conditions are: heating from room temperature to 150°C at a heating rate of 2°C / min, keeping at 150°C for 1 hour, heating from 150°C to 400°C at a heating rate of 0.15°C / min, keeping for 2 hours, and then heating from 400°C to 450°C at a heating rate of 0.8°C / min, and keeping for 2 hours.
[0044] Sintering treatment: The sintering conditions are: heating to 1400°C at a heating rate of 1.5°C / min, keeping the temperature for 2 hours, and then cooling naturally to room temperature to obtain a ceramic matrix, wherein the yttria content in the yttria-stabilized zirconia is 2.3% by molar ratio. The thermal expansion coefficient of the ceramic matrix is 10×10 -6 / ℃.
[0045] (2) The ceramic sheet was subjected to rough sandblasting treatment. During sandblasting, silicon carbide sand particles with a spherical appearance and an average particle size of 20 μm were selected as the sandblasting material. The sandblasting direction was 30° to the surface of the ceramic sheet to be treated. The sandblasting time was 10 s and the working pressure during sandblasting was 0.7 MPa.
[0046] (3) The surface of the ceramic sheet obtained by sandblasting is finely polished for 60 seconds on a polishing machine with diamond abrasive paste to obtain a surface-strengthened yttria-stabilized zirconia ceramic material.
[0047] Example 2
[0048] The difference from Example 1 is:
[0049] (2) The ceramic sheet was subjected to rough sandblasting treatment. During sandblasting, zirconium oxide sand particles with a spherical appearance and an average particle size of 100 μm were selected as the sandblasting material. The sandblasting direction was 50° to the surface of the ceramic sheet to be treated. The sandblasting time was 100 s and the working pressure during sandblasting was 0.5 MPa.
[0050] Example 3
[0051] The difference from Example 1 is:
[0052] (2) The ceramic sheet was subjected to rough sandblasting treatment. During sandblasting, zirconia-toughened alumina sand particles with a spherical appearance and an average particle size of 200 μm were selected as the sandblasting material. The sandblasting direction was 80° to the surface of the ceramic sheet to be treated. The sandblasting time was 150 s and the working pressure during sandblasting was 0.2 MPa.
[0053] Example 4
[0054] The difference from Example 1 is that the yttria content in the yttria-stabilized zirconia is 2% by molar ratio; and the monoclinic phase content of the prepared matrix layer is 0.5%.
[0055] Example 5
[0056] The difference from Example 1 is that the yttria content in the yttria-stabilized zirconia is 2.8% by molar ratio; and the monoclinic phase content of the prepared matrix layer is 1.5%.
[0057] Example 6
[0058] The difference from Example 1 is that the yttria content in the yttria-stabilized zirconia is 3% by molar ratio; and the monoclinic phase content of the prepared matrix layer is 2%.
[0059] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the yttria-stabilized zirconia ceramic material is not subjected to step (2) and step (3).
[0062] Comparative Example 2
[0063] The difference from Example 1 is that white corundum sand particles with a flaky appearance and an average particle size of 20 μm are selected as the sandblasting material during the sandblasting rough polishing process.
[0064] Comparative Example 3
[0065] The difference from Example 1 is that the ceramic sheet is subjected to surface sandblasting and rough polishing treatment. When sandblasting, sand particles with a spherical appearance and an average particle size of 8 μm are selected as sandblasting materials. The sandblasting direction is at an angle of 30° to the surface to be treated of the ceramic sheet. The sandblasting time is 200 s, and the working pressure during sandblasting is 1.2 MPa.
[0066] The following tests were performed on the yttria-stabilized zirconia ceramic materials obtained in the above embodiments and comparative examples:
[0067] (1) Monoclinic phase content: measured by X-ray polycrystal diffraction analyzer;
[0068] (2) Depth of strengthening layer: measured by X-ray polycrystal diffractometer or Raman spectroscopy;
[0069] (3) Four-point bending strength test: measured using a universal mechanical testing machine, the test standard refers to GBT 6569-2006;
[0070] (4) Drop ball test: Take 10 pieces of yttria-stabilized zirconia ceramic materials with a thickness of 0.55 mm and a length and width of 50 mm for the drop ball test. The drop ball test uses a 32 g steel ball, which starts to fall freely from a height of 5 cm. If the sample does not break after impact, the height of the steel ball is increased by 5 cm and the test is continued until the ceramic breaks. The height at this time is recorded as the drop ball height of the ceramic material. The drop ball test height is the average value of the above 10 pieces of yttria-stabilized zirconia ceramic material samples and is recorded as the drop ball test height of the sample.
[0071] Table 1 Summary of test results of ceramic materials obtained in various embodiments and comparative examples
[0072] Monoclinic phase content of strengthening layer Monoclinic phase content in matrix Strengthening layer depth Four-point bending strength Drop ball test height Example 1 6% 1% 1 μm 1200 MPa 25 cm Example 2 30% 1% 1.5 μm 1280 MPa 30 cm Example 3 40% 1% 3 μm 1200 MPa 25 cm Example 4 6% 0.5% 1 μm 1200 MPa 25 cm Example 5 30% 1.5% 1.5 μm 1280 MPa 30 cm Example 6 40% 2% 3 μm 1200 MPa 25 cm Comparative Example 1 / 1% / 1100 MPa 20 cm Comparative Example 2 5% 1% 0.5 μm 1150 MPa 20 cm Comparative Example 3 4.5% 1% 2 μm 900 MPa 20 cm
[0073] As can be seen from the above table, the four-point bending strength of Examples 1-6 of the present invention is greater than or equal to 1200MPa, and the height of the falling ball test is greater than or equal to 25cm. Compared with Comparative Examples 1-3, the four-point bending strength and the height of the falling ball test are improved. The additional strengthening layer on the ceramic surface effectively improves the bending strength and resistance to falling ball damage of the material, and improves the performance of the material. Comparative Example 2 of the present invention uses a sheet-like sandblasting material, while Examples 1-6 all use a spherical sandblasting material. By comparison, it can be seen that although the sheet-like sandblasting material can also increase the content of the monoclinic phase in the surface layer, it is easy to cause scratches on the ceramic surface, increase the path of crack propagation, and thus reduce the performance of the ceramic material.
[0074] Compared with Comparative Example 3, the blasting conditions such as the particle size of the blasting material and the duration are outside the scope of the present invention, and a ceramic material with high strength cannot be obtained.
[0075] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A method for preparing yttria-stabilized zirconia ceramic material, characterized in that: The following steps are involved: (1) forming a yttrium-stabilized zirconia ceramic raw material into a ceramic matrix blank, and sequentially performing degreasing and sintering treatments on the ceramic matrix blank to obtain a ceramic sheet; (2) The ceramic sheet is subjected to rough sandblasting treatment. When sandblasting, a spherical sandblasting material with an average particle size of 10-300 μm is selected. The sandblasting direction is at an angle of 30-90° to the surface of the ceramic sheet to be treated. The sandblasting time is 5-180 s and the working pressure during sandblasting is 0.1-1.0 MPa. (3) fine polishing the surface of the ceramic sheet obtained by the sandblasting, and fine polishing the roughly polished ceramic sheet on a polishing machine with a polishing paste or a polishing solution until there are no scratches on the sample surface, thereby obtaining the yttria-stabilized zirconia ceramic material. The ceramic material comprises a matrix layer and at least one strengthening layer adjacent to the matrix layer, wherein the crystal phase of the ceramic material comprises a monoclinic phase and a tetragonal phase, wherein the weight percentage of the monoclinic ceramic in the matrix layer is 0.1-8% of the ceramic material of the matrix layer, the weight percentage of the monoclinic ceramic in the strengthening layer is 5-40% of the ceramic material of the strengthening layer, the monoclinic phase content in the matrix layer is 2%-20% of the monoclinic phase content in the strengthening layer, and the thickness of the strengthening layer is 0.5-5 μm.
2. The preparation method according to claim 1, characterized in that The yttria-stabilized zirconia ceramic material has an yttria content of 2.1 mol%-3.2 mol%, a colorant molar ratio of 0-5%, and the rest is zirconia.
3. The preparation method according to claim 1, characterized in that: The monoclinic phase content of the matrix layer is 0.1-3%, the monoclinic phase content of the strengthening layer is 5-30%, and the monoclinic phase content in the matrix layer is 2%-18% of the monoclinic phase content in the strengthening layer.
4. The preparation method according to claim 1, wherein the strengthening layer has a thickness of 0.5 to 3 μm.
5. The preparation method according to claim 1, characterized in that: The yttria content of the yttria-stabilized zirconia ceramic material raw material is 2.5 mol%-3 mol%, and the zirconia content is 97 mol%-97.5 mol%.
6. The preparation method according to claim 1, characterized in that: In step (1), the sintering temperature is 800°C-1400°C, and the sintering time is 0.5-4h.
7. The preparation method according to claim 1, characterized in that: In step (2), the sandblasting material is one or more of alumina, silicon carbide, zirconium oxide, and zirconium oxide toughened alumina.
8. The preparation method according to claim 1, characterized in that: In step (3), the grinding paste or polishing grinding solution contains one or more of aluminum oxide, silicon oxide, and diamond.
Citation Information
Patent Citations
Shaped sintered ceramic bodies composed of y2o3-stabilized zirconium oxide and process for producing a shaped sintered ceramic body composed of y2o3-stabilized zirconium oxide
CN104159870A